A Quality control study on Alucast International Manufacturing Incorporated - Bernarte, Alfredo L. Jr; Bides, Emmuel John T.; Inocencio, Romeo F.; Lomabao, Lawrence P. (College of Engineering, 1997)
The study group evaluated the quality procedures of Alucast International Manufacturing Incorporated. Records show that the main area for improvement is the Casting Process because of its high percentage of rejects. The company's Quality Control Department is only at its infancy stage, and the company is open to a lot of opportunities for improvement in their quality system. After, analyzing the company's quality system and in-process quality control records, the group finds that the quality system has not been able to improve on the percent defectives produced by the casting process. Quality Control data further revealed that production is at present not capable of meeting a very high demand for its products. As a whole, the current quality control system is suffering from a 15 percent-20 percent defects which the company aims to reduce to about 10 percent. Though the study group recognizes the inconsistent nature of the casting process, an ideal and dynamic quality system should include a systematic plan for improving the quality level of the company towards a performance of 0 percent defects. This is why the focus of the study has been on the casting process. Among the recommendations that the group has forwarded, the hiring of a consultancy firm and/or I.E. would be the most beneficial to the company since every aspect towards improvement of not only the Quality System but the entire Production Process can be effectively analyzed and given the proper attention. As a whole, the Quality Improvement Process aims to reduce the percent defectives of the company in the casting process in order for the company to reach a higher level in terms of Total Quality Strategy.